Direct admission to the hospital: An alternative approach to hospitalization. Issue 4 (20th November 2015) - Leyenaar, JoAnna K.; Lagu, Tara; Lindenauer, Peter K.
Abstract : Appropriate use of emergency departments (EDs) is a focus of national healthcare reform efforts, and patients requiring hospital admission account for a substantial proportion of ED utilization. Despite this, little attention has been paid to evaluating direct admission to the hospital as an alternative to hospital admissions beginning in the ED. In this Perspective, we discuss the role of hospital medicine in the changing epidemiology of hospital admissions, the potential risks and benefits of direct admission to the hospital, and the need for research to evaluate the safety and effectiveness of this admission approach. We propose that transitions of care research and quality improvement, historically focused on hospital‐to‐home transitions, be expanded to address transitions into the hospital. Journal of Hospital Medicine 2016;11:303–305. © 2015 Society of Hospital Medicine